"Because I Was Sick": Seriously Ill Veterans' Perspectives on Reason for 30‐Day Readmissions. Issue 3 (2nd March 2015) - Enguidanos, Susan; Coulourides Kogan, Alexis M.; Schreibeis‐Baum, Hannah; Lendon, Jessica; Lorenz, Karl
Abstract : Objectives: To determine the perspectives of seriously ill individuals on reasons for 30‐day hospital readmission. Design: A prospective qualitative study was conducted employing individual interviews conducted at bedside. Setting: Department of Veterans Affairs Greater Los Angeles Healthcare System. Participants: Seriously ill individuals with heart failure or cancer receiving inpatient palliative care and readmitted to the hospital within 30 days of hospital discharge were recruited to participate. Nine were interviewed. Measurements: A semistructured interview protocol was used to elicit participant perspectives on readmission causes. Results: All participants were male and had a mean age of 70.1 ± 9.5. Participants were ethnically diverse (three African Americans, three Caucasians, three Hispanic or mixed ethnic background). Six lived alone, and four did not have caregiver support. Qualitative analysis of transcripts revealed three themes relating to reasons for hospital readmission: lack of caregiver support and motivation to provide self‐care, acceptance of condition and desire for aggressive care, and access to care and poor quality of care. Conclusion: Participants identified potentially avoidable reasons for hospital readmission as well as causes that require rethinking regarding how community support is targeted and delivered. Participant preference for aggressive care, inability to provide self‐care, and lack of caregiver support suggest the need for new and innovative mechanisms to support seriously ill community‐dwelling individuals.